The History of Governance Reform and the Anti-corruption Measure under Guided Democracy era: Indonesia experience in 1957 – 1967 - Juwono, Vishnu (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2018)
This article highlighted how the last parliamentary system government reached the verge of collapse due to both Sukarno and Nasution’s restlessness regarding what they saw as a corrupt politician that made parliamentary democracy dysfunctional and ignored people’s interests. The partnership between Sukarno and Nasution was formed to establish a new political governance structure that was underpinned by the army’s more assertive role in politics, called Guided Democracy. The article showed the disunity between Hatta and Nasution which is resulted in a disjointed effort towards governance reform and anti-corruption initiatives that was later dismantled by Sukarno and his supporter. This article used a range of primary sources including diplomatic correspondents, memo, reports issued by the United Kingdom (UK) Foreign Commonwealth Office (FCO) and the Australia Department of Foreign Affairs. In complementing these data from the UK and the Australia Government, this article used other primary resources from Indonesian government such as relevant laws, presidential decrees and government regulations, presidential speeches, international donor reports or documents and national as well as international article newspaper. The main contribution of this article was to provide an ingrained account of Sukarno’s Guided Democracy era in the context of governance reform and anti-corruption initiatives, which is currently lacking in the current academic corpus on Indonesia’s politics of public policy.